Efficacy of a coating composed of chitosan from Mucor circinelloides and carvacrol to control Aspergillus flavus and the quality of cherry tomato fruits - de Souza, Evandro L.; Sales, Camila V.; de Oliveira, Carlos E. V.; Lopes, Laênia A. A.; da Conceição, Maria L.; Berger, Lúcia R. R.; Stamford, Thayza C. M. (Frontiers in Microbiology, 2015)
Cherry tomato (Lycopersicon esculentum Mill) fruits are susceptible to contamination by Aspergillus flavus, which may cause the development of fruit rot and significant postharvest losses. Currently there are significant drawbacks for the use of synthetic fungicides to control pathogenic fungi in tomato fruits, and it has increased the interest in exploring new alternatives to control the occurrence of fungal infections in these fruits. This study evaluated the efficacy of chitosan (CHI) from M. circinelloides in combination with carvacrol (CAR) in inhibiting A. flavus in laboratory media and as a coating on cherry tomato fruits (25 °C, 12 days and 12 °C, 24 days). During a period of storage, the effect of coatings composed of CHI and CAR on autochthonous microflora, as well as on some quality characteristics of the fruits such as weight loss, color, firmness, soluble solids and titratable acidity was evaluated. CHI and CAR displayed MIC values of 7.5 mg/mL and 10 µL/mL, respectively, against A. flavus. The combined application of CHI (7.5 or 3.75 mg/mL) and CAR (5 or 2.5 µL/mL) strongly inhibited the mycelial growth and spore germination of A. flavus. The coating composed of CHI (3.75 mg/mL) and CAR (2.5 or 1.25 µL/mL) inhibited the growth of A. flavus in artificially contaminated fruits, as well as the native fungal microflora of the fruits stored at room or low temperature. The application of the tested coatings preserved the quality of cherry tomato fruits as measured by some physicochemical attributes. From this, composite coatings containing CHI and CAR offer a promising alternative to control postharvest infection caused by A. flavus or native fungal microflora in fresh cherry tomato fruits without negatively affecting their quality over storage.